Establishment and characterization of an hACE2/hTMPRSS2 knock-in mouse model to study SARS-CoV-2 - Liu, Hongwei; Brostoff, Terza; Ramirez, Ana; Wong, Talia; Rowland, Douglas J.; Heffner, Mollie; Flores, Arturo; Willis, Brandon; Evans, Jeffrey J.; Lanoue, Louise; Lloyd, K. C. Kent; Coffey, Lark L. (Frontiers in Immunology, 2024)
Despite a substantial body of research, we lack fundamental understanding of the pathophysiology of COVID-19 caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) including pulmonary and cardiovascular outcomes, in part due to limitations of murine models. Most models use transgenic mice (K18) that express the human (h) angiotensin converting enzyme 2 (ACE2), ACE2 knock-in (KI) mice, or mouse-adapted strains of SARS-CoV-2. Further, many SARS-CoV-2 variants produce fatal neurologic disease in K18 mice and most murine studies focus only on acute disease in the first 14 days post inoculation (dpi). To better enable understanding of both acute (<14 dpi) and post-acute (>14 dpi) infection phases, we describe the development and characterization of a novel non-lethal KI mouse that expresses both the ACE2 and transmembrane serine protease 2 (TMPRSS2) genes (hACE2/hTMPRSS2). The human genes were engineered to replace the orthologous mouse gene loci but remain under control of their respective murine promoters, resulting in expression of ACE2 and TMPRSS2 instead of their murine counterparts. After intranasal inoculation with an omicron strain of SARS-CoV-2, hACE2/hTMPRSS2 KI mice transiently lost weight but recovered by 7 dpi. Infectious SARS-CoV-2 was detected in nasopharyngeal swabs 1-2 dpi and in lung tissues 2-6 dpi, peaking 4 dpi. These outcomes were similar to those in K18 mice that were inoculated in parallel. To determine the extent to which hACE2/hTMPRSS2 KI mice are suitable to model pulmonary and cardiovascular outcomes, physiological assessments measuring locomotion, behavior, and reflexes, biomonitoring to measure cardiac activity and respiration, and micro computed tomography to assess lung function were conducted frequently to 6 months post inoculation. Male but not female SARS-CoV-2 inoculated hACE2/hTMPRSS2 KI mice showed a transient reduction in locomotion compared to control saline treated mice. No significant changes in respiration, oxygen saturation, heart rate variability, or conductivity were detected in SARS-CoV-2 inoculated mice of either sex. When re-inoculated 6 months after the first inoculation, hACE2/hTMPRSS2 KI became re-infected with disease signs similar to after the first inoculation. Together these data show that a newly generated hACE2/hTMPRSS2 KI mouse can be used to study mild COVID-19.